Seven for a secret [compact disc, unabridged] - Faye, Lyndsay (Dreamscape Media, Llc, 2013)
Six months after the formation of the NYPD, its most reluctant and talented officer, Timothy Wilde, thinks himself well versed in his city's dark practices, until he learns of the gruesome underworld ruled by the 'blackbirders, ' who snatch free Northerners of color, masquerade them as slaves, and sell them South to toil as plantation property.